Effects of cognitively engaging physical activity interventions on executive function in children and adolescents: a systematic review and meta-analysis - Mao, Fan; Huang, Fang; Zhao, Shan; Fang, Qun (Frontiers in Psychology, 2024)
Background This systematic review and meta-analysis aim to evaluate the effects of cognitively engaging Physical Activity (PA) interventions on Executive Function (EF) in children and adolescents. It examines how different intervention modalities, durations, frequencies, and session lengths influence these effects. Methods We followed the PRISMA guidelines and searched PubMed, SPORTDiscus, Embase, and Web of Science for relevant studies. Studies were included if they were Randomized Controlled Trials (RCTs) focusing on PA with cognitive elements targeting EF in healthy children and adolescents. Data were extracted and effect sizes computed using Standardized Mean Differences (SMDs). Results From an initial 1,635 articles, 23 studies with 2,857 participants were included. The overall effect of cognitively engaging PA on EF was significant (SMD = 0.32, 95% CI 0.14–0.51), with notable improvements in inhibitory control (SMD = 0.35) and working memory (SMD = 0.34). High heterogeneity was observed (I2 = 91.1%). Moderator analyses revealed that interventions lasting more than 6 weeks, with sessions over 20 min and conducted more than twice a week, were particularly effective. Conclusion Cognitively engaging PA interventions positively impact EF in children and adolescents, particularly in inhibitory control. Effective interventions are characterized by longer duration, higher frequency, and extended session lengths. These findings underscore the importance of integrating cognitive challenges within PA programs to enhance EF, warranting future research and practical applications in educational and developmental settings.